Marine applications of ferrocement. - Trinidad, A.G (Philippine Engineering Journal)
Ferrocement has been accepted as a suitable building material for marine structures. However, its potentials have not been fully utilized. The reasons are manifold. This study identifies and analyzes the problem areas, the possible solutions and the improvement of ferrocement marine technology.